Injuries in Elite Men's Lacrosse: An Observational Study During the 2010 World Championships. Issue 7 (27th July 2014) - Webb, Mark; Davis, Caroline; Westacott, Daniel; Webb, Robin; Price, Jessica
Background: There are limited data on injuries sustained during men's lacrosse. As the sport gains popularity, practitioners will be more likely to treat lacrosse players. Purpose: To analyze data from the 2010 World Lacrosse Championships. Study Design: Descriptive epidemiology study. Methods: This was a prospective observational study of injuries reported during the 2010 World Lacrosse Championships. An injury surveillance questionnaire was completed, and data were categorized into body part injured, diagnosis, mechanism, and time of injury. Results: Over 9 days, 667 players from 29 countries competed in 105 games. A total of 150 injuries were sustained by 129 individuals aged 16 to 46 years. Five times more injuries occurred during games than in training (69.3% [n = 104] vs 13.3% [n = 20]; rate ratio [95% CI] = 5.2 [4.9-5.5]), resulting in 39.5 injuries per 1000 hours played. The most frequent mechanism was contact (53.3%; n = 80), including direct impact with another player (30%; n = 45), with a stick (16.7%; n = 25), or with a ball (5.3%; n = 8). Change of direction and/or speed were the most common noncontact mechanisms (27.3%; n = 41). The most frequently reported injuries were contusions (32.0%; n = 48), sprains (22.7%; n = 34), and strains (22.7%; n = 34). The lower limb was the most injured body part (50.7%; n = 76) compared with the upper limb (23.3%; n = 35; rate ratio [95% CI] = 2.2 [2.1-2.3]). The ankle was the most injured joint (14.0%; n = 21), followed by the shoulder (10.0%; n = 15). Conclusion: As participation expands, health professionals may become more responsible for treating lacrosse players. Players are susceptible to a range of injuries. Familiarity with the common injury patterns could help treatment and prevention. Despite differences in rules during international competition, this study corroborates reports from North America. Clinical Relevance: The epidemiology of men's lacrosse injuries needs to be documented and understood to effectively prevent injuries. The 2014 World Championships are to be held in Denver, Colorado (July 10-19, 2014), and it is important that practitioners treating players are aware of the differences in the international game. Publication of these data will allow for those planning lacrosse tournaments to do so more effectively.